2014
DOI: 10.1097/00007890-201407151-00316
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Dimethylarginine as Predictor of Graft Loss and All-Cause Mortality in Renal Transplant Recipients.

Abstract: Background. Elevated symmetric dimethylarginine (SDMA) has been shown to predict cardiovascular events and all cause mortality in diverse populations. The potential role of SDMA as a risk marker in renal transplant recipients (RTR) has not been investigated. Methods. We analyzed SDMA in the placebo arm of the Assessment of Lescol in Renal Transplantation study, a randomized controlled trial of fluvastatin in RTR. Mean follow-up was 5.1 years. Patients were grouped into quartiles based on SDMA levels at study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A relationship between SDMA and mortality independent of GFR has also been reported in renal transplant recipients. 36 Recent evidence suggests potential direct pathophysiological links between SDMA and cardiovascular disease through indirect inhibition of nitric oxide synthesis. 15 The proposed mechanism is through competition with L-arginine for transport, thereby limiting the availability of L-arginine to nitric oxide synthase.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between SDMA and mortality independent of GFR has also been reported in renal transplant recipients. 36 Recent evidence suggests potential direct pathophysiological links between SDMA and cardiovascular disease through indirect inhibition of nitric oxide synthesis. 15 The proposed mechanism is through competition with L-arginine for transport, thereby limiting the availability of L-arginine to nitric oxide synthase.…”
Section: Discussionmentioning
confidence: 99%
“…[12] With respect to SDMA, initial studies did not find an association with adverse outcomes, [7,13,14] but some more recent studies reported positive associations with all-cause mortality or CVD. [11,15,16] Overall, prior studies on ADMA/SDMA and CVD or all-cause mortality were derived from many different study populations (general population, [15,17,18] patients with CVD, [9,11,19,20] renal diseases, [7,13,[21][22][23][24] diabetes, [25,26] or critically ill patients from intensive care unit,[27-29] respectively), differed in their methodological approaches (e.g. using types of samples (plasma vs. serum) or methods to determine the biomarker levels (HPLC vs. tandem mass spectroscopy vs. ELISA), or considered different confounders in their analysis.…”
Section: Introductionmentioning
confidence: 99%